2018
DOI: 10.7771/2159-6670.1180
|View full text |Cite
|
Sign up to set email alerts
|

How Nationality, Weather, Wind, and Distance Affect Consumer Willingness to Fly in Autonomous Airplanes

Abstract: Several studies have examined passengers' trust in human-operated systems versus autonomous systems. Prior studies have also reported cultural differences among individuals from India and the United States. The purpose of this study was to investigate how nationality, weather, wind, and distance affect passengers' willingness to fly in autonomous aircraft. Participants included 161 volunteers from the United States and 137 volunteers from India. In 12 different conditions, participants were asked to rate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The perceived threat from COVID-19 is very real, and people are afraid for various reasons including losing their employment, becoming seriously ill, transmitting the disease to family or friends, being responsible for their death and suffering, and general financial loss associated with the virus ( Conway et al, 2020 ; Spitzmuller et al, 2020 ). There has been considerable research examining consumer willingness to fly in a variety of situations ( Anania et al, 2018a , Anania et al, 2018b ; Bergstrom and McCaul, 2004 ; Ragbir et al 2018 ; Rice and Winter 2015 ; Rice et al, 2015 ; Winter et al, 2017 ). However, to date, no study that we know of has identified the factors that predict what type of person is willing to fly during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived threat from COVID-19 is very real, and people are afraid for various reasons including losing their employment, becoming seriously ill, transmitting the disease to family or friends, being responsible for their death and suffering, and general financial loss associated with the virus ( Conway et al, 2020 ; Spitzmuller et al, 2020 ). There has been considerable research examining consumer willingness to fly in a variety of situations ( Anania et al, 2018a , Anania et al, 2018b ; Bergstrom and McCaul, 2004 ; Ragbir et al 2018 ; Rice and Winter 2015 ; Rice et al, 2015 ; Winter et al, 2017 ). However, to date, no study that we know of has identified the factors that predict what type of person is willing to fly during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in 2018, surveyed passengers noted potential benefits of automated flight such as: decreases in pilot fatigue, human error, and low costs for automated aircraft [32]. However, the benefits were generally outweighed by concerns over reliability, system security, lack of a human pilot, and operation under extreme conditions, such as rain, snow, and ice.…”
Section: ) Remote Pilot License and Training Requirementsmentioning
confidence: 99%
“…In this regard, a study conducted by Yedavalli and Mooberry (2019) observed that about 44% of people support the UAM initiative. People expect cost reductions for autonomous vehicles, decreased pilot fatigue, and minimal manual error for UAM (Ragbir et al, 2018). Studies find that positive public perceptions of acceptance of autonomous vehicles significantly reduce psychological costs associated with adopting this technology (Penmetsa et al, 2019;Park, 2021).…”
Section: Introductionmentioning
confidence: 99%